Effectiveness Of Oral Curcumin Administration On The Natural Mucosa Of Wistar Rats After Exposure To Electric Cigarettes Smoke - Syahreza, M.; Punagi, Abdul Qadar; Djufri, Nani Iriani; Salam, Abdul (Journal of Neonatal Surgery, 2025)
Backgroundː Exposure to e-cigarettes in human bronchial epithelial cells was found to induce mucociliary airway dysfunction in vitro. Additionally, e-cigarettes were shown to reduce the viability of gingival epithelial cells and promote cell apoptosis or necrosis. Methodsː The experimental study (true experimental design) employed a control group and a treatment group, with simple randomization of 20 Wistar rats per group, resulting in a total of 40 Wistar rats in the study. Then histopathological examination was performed to assess tissue damage. Resultsː Research resultsshowed that 400 mg curcumin provided effective protection against nasal mucosal damage caused by e-cigarette smoke exposure, by reducing the severity of epithelial disarrangement, erosion, inflammation, and epithelial metaplasia. However, mild to moderate histopathological changes still occurred, so additional approaches are needed for more optimal protection Conclusionsː It can be concluded that there is a relationship between the effectiveness of oral curcumin administration on the nasal mucosa of Wistar rats after exposure to electronic cigarette smoke.